EFEKTIVITAS MULTIMEDIA DALAM PEMBELAJARAN MODA DARING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V SEKOLAH DASAR PADA MATERI SISTEM PENCERNAAN - Connyta Elvadola; Mareyke Jessy Tanod (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
This study aims to determine the effectiveness of the use of multimedia on student learning outcomes. The problem in this research is the decline in student learning outcomes during the implementation of the online mode or distance learning (PJJ) established by the government. This study used purposive sampling. The instrument used in this study was a test. The results of the data analysis showed that there was a significant impact of the use of multimedia on the learning outcomes of class V SDN 02 Sumur Putri Bandar Lampung. This is shown by the Wilcoxon pretest and posttest results showing the sig value of 0.000 <0.05, so that the use of multimedia can be an alternative to improve student learning outcomes in online mode learning.